Clinical outcomes of frozen-thawed single blastocyst transfer in patients requiring whole embryo freezing. (3rd March 2016) - He, Qiao-hua; Wang, Lu; Liang, Lin-lin; Zhang, He-long; Zhang, Cui-lian; Li, Hang-sheng; Cui, Shi-hong
ABSTRACT: We compared clinical outcomes amongst frozen-thawed cleavage-stage embryo, double and single blastocyst transfers in patients requiring whole embryo freezing. Data of infertile patients undergoing in-vitro fertilization and embryo transfer (IVF-ET) in our Reproductive Medicine Center from January 2010 to December 2012 were retrospectively analyzed. According to patients' wishes, patients were divided into cleavage-stage embryo transfer groups (group A, n = 456), double blastocyst transfer group (group B, n = 106), and single blastocyst transfer group (group C, n = 402). We found that the number of frozen embryos was significantly less in groups B and C than in group A (all p < 0.05), but the implantation rate was significantly higher in groups B and C as compared to group A (all p < 0.05). The clinical pregnancy rate and pregnancy rate per included cycle were significantly higher in group B than in groups A and C (all p < 0.05). The multiple pregnancy rate was significantly lower in group C than in groups A and B (all p < 0.05). The rate of early abortion was significantly lower in group C as compared to group A ( p < 0.05). The data support the view that it may be the best clinical strategy for patients who require whole embryo freezing and have four or more Day 3 embryos available, to incubate Day 3 embryos into blastocysts, which are then vitrified for elective single blastocyst transfer.